Youth character building anti-pornography in South East Asia - Nur Kholisoh; Mohamad Saifudin Mohamad Saleh; Siti Muslihatul Mahmudah; Nurzali Ismail (Penerbit Universiti Kebangsaan Malaysia, 2022)
Media effects are one of the ten problems youths face today. Pornography is media content that causes a lot of negative effects on youth. Social media today exposes a lot of pornographic content that can be easily accessed by youth. At the same time, pornography among youth is a serious issue in Southeast Asian countries. Indonesia and Malaysia are countries in Southeast Asia with similar social and cultural backgrounds. The parents play an important role in preventing the impact of pornography among youth. Additionally, youth’s perceptions of pornography also play a role in shaping anti-pornography behaviours. This research aimed to analyse the influence of communication between parents and youth and youth’s perceptions of pornography on the formation of anti-pornography behaviour and attitudes. The population in this study were youth in 4 cities in Indonesia and Malaysia. This research used the cluster purposive sampling technique to determine samples from each cluster based on specific considerations (purposive), with an age range of 20-24 years. Based on the Slovin formula, the total sample obtained is 800 respondents. This study used path analysis as a data analysis technique. The results showed that communication between parents and youth did not have a direct and significant influence on the formation of anti-pornography behaviours. Meanwhile, youth’s perception of pornography has a direct and significant influence on developing anti-pornography behaviours. Most respondents thought that pornographic scenes on social media do not conform to religious values and that watching pornographic content on social media is addictive.